Scientometric mapping of global publications on pulmonary embolism in Covid-19 research - Shettar, Iranna; Hadagali, Gururaj S.; Timanaykar, Ramesh (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. The study presents scientometric research on the scientific literature on COVID-19 associated with Pulmonary Embolism indexed in the Web of Science database. Design/Methodology/Approach. The study analysed 1307 bibliographic records published between 2020 and April 10, 2023. The authors analysed the publication and citation data for the parameters like key participating countries, organisations, authors, journals, and publishers. Collaborative patterns were studied through science mapping tools like VOSviewer and Biblioshiny (R Package). Results/Discussion. The study analysed 1307 publications, which received 38,930 citations, at the rate of 29.79 Citations Per Paper. The study also presented the publication growth rate (Annual Growth Rate -47.87%), 97.55% collaborated publications, and 21.88% of publications are through international collaboration. 9,523 authors from 87 countries and 2,643 organisations participated in these research publications. The USA (368), Italy (205), and England (135) were the most productive countries. Udice French Research Universities (87), INSERM (72) and Assistance Publique Hopitaux Paris (62) were the top contributing organisations. F.A. Klok of Leiden Univ Med Ctr, Leiden, Netherlands (21) has a highly published author. Thrombosis Research (59), a journal published by Elsevier, is the highly preferred journal to publish the research. Journal of Thrombosis and Haemostasis (2602), published by Wiley, is a highly referred journal among the 22,080 references. Elsevier has published the highest number of 326 research papers on ‘Covid 19 and Pulmonary Embolism’ publisher among the 115 publishers. The top 5 keywords in terms of frequency of occurrences were: covid-19 (714), pulmonary embolism (405), sars-cov-2 (191), thrombosis (154), and venous thromboembolism (146). Conclusions. The present study provides a framework to profile the research landscape and exploit the global research on the scientific literature on COVID-19 associated with Pulmonary Embolism, combining the productivity analysis and its impact through citation analysis. A summary of the study throws light on the research opportunities for doctors and researchers, along with the implications for various healthcare systems and policymakers.